Odpowiedzi

  • Użytkownik Zadane
2010-03-16T23:42:50+01:00
Cześć Kamila ;p

Trzymaj:
(1/2*16+1/3*3)^-1*[4+2*1/9]^-1*(-19)=(8+1}^-1*[4+2/9]^-1*(-19)=1/9*[1/4+9/2]*(-19)=1/9*(1/4+18/4)*(-19)=1/9*19/4*(-19/1)=-361/36=-10 całych i 1/36

Chyba to jest dobry wynik ;p
^ - potęga
2010-03-16T23:49:55+01:00
(2do -1 * 4²+3do-1*3)do-1[2²+(₁½)do-1*3do -2]*(-19)=
(½*16+⅓*3)do-1[4+(3/2)do-1*(⅓)²]*(-19)=
(8+1)do-1[4+(⅔)*1/9]*(-19)=
9do-1[4+2/27]*(-19)=
1/9[4i2/27]*(-19)=
1/9[110/27]*(-19)=
110/243*(-19)=
-2090/243=-8i146/243